2008
DOI: 10.1177/0192623308318216
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Hepatic Effects of Perfluorooctanoic Acid and WY 14,643 in PPAR-α Knockout and Wild-type Mice

Abstract: Perfluorooctanoic acid (PFOA) is a chemical used in the production of fluoropolymers. Its persistence in the environment and presence in humans and wildlife has raised health concerns. Liver tumor induction by PFOA is thought to be mediated in rodents by PPAR-α. A recent US EPA scientific advisory board questioned the contribution of PPAR-α in PFOA-induced liver tumors. Liver response in CD-1, SV/129 wild-type (WT), and PPAR-α knockout (KO) SV/129 mice was evaluated after seven daily treatments of PFOA-NH 4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
89
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 30 publications
14
89
1
Order By: Relevance
“…Since PFOA is an agonist of peroxisome proliferator-activated receptor (PPAR)-alpha, the PFOAinduced liver enlargement is attributed to the effect on PPAR-alpha (Chevalier et al, 2000;Wolf et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since PFOA is an agonist of peroxisome proliferator-activated receptor (PPAR)-alpha, the PFOAinduced liver enlargement is attributed to the effect on PPAR-alpha (Chevalier et al, 2000;Wolf et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Published reports indicated that PFOA induced increases in hepatocyte hypertrophy, ultrastructural alterations of peroxisome proliferation (Wolf, Moore, et al 2008), and gene expression changes related to PPARa activation ) in SV/129 mice. However, PFOA and PFOS also induced gene expression changes that were independent of PPARa for xenobiotic and fatty acid metabolism, inflammation, and cell cycle regulation in PPARa null mice (Rosen et al , 2010.…”
Section: Treatmentmentioning
confidence: 98%
“…It has been proposed that carbon chain length correlates positively with activity and adverse effects of PFAS compounds (Goecke-Flora and Reo 1996; Kudo et al 2006;Wolf, Moore, et al 2008;Buck et al 2011), which suggests that the 10-carbon PFDA should induce a higher degree of immune suppression as compared to shorter-chain compounds. However, variability in potency and mode of action have been observed between PFOA and PFOS, both 8-carbon compounds and the most commonly studied PFAS.…”
Section: Treatmentmentioning
confidence: 99%
“…Both Wy14,643 and PFOA increased hepatic cell proliferation in wild-type mice (see Wolf et al, 2008), and among the genes up-regulated by either compound were Ccnd1 (Cyclin D1) and cJun (Figure 7). Ccnd1 is a cyclin gene involved in progression of cells through the G 1 phase of the cell cycle, whereas cJun, a component of AP-1, has been shown to positively influence hepatocyte proliferation during liver regeneration (Stepniak et al, 2006) and is a potential upstream regulator of Ccnd1 (Wisdom et al, 1999).…”
Section: Gene Expression Changes In Wild-type Micementioning
confidence: 99%